Noise Qualification in Bali Palm Leaf Image with Gaussian Filter Method - Prathama, Wayan Adhitya; Arta Wibawa, I Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 3 (2020): JELIKU Volume 8 No 3, February 2020, 2020)
In improving the quality of the image basically makes the appearance of an image better than before. One thing that is done in improving the image quality is noise qualification. This noise qualification aims to reduce the level of noise contained in a digital image. In this study, the image used is the image of Bali palm leaf. There are many methods that can be used to qualify for noise. One of them is the Gaussian filter. In this study, Gaussian Filter is used as a method to qualify the noise contained in the palm leaf image. The image quality after the noise qualification process is calculated using PSNR (Peak Signal to Noise Ratio). The higher the PSNR value obtained, the better the image quality. In this study, the PSNR value obtained in the palm leaf image after processing the noise qualification is 54.7625 db. Keywords : Gaussian Filter, Noise, PSNR, Bali Palm Leaf, Image